Distinctive features of the D101N and D101G variants of superoxide dismutase 1; two mutations that produce rapidly progressing motor neuron disease. (21st October 2013) - Ayers, Jacob; Lelie, Herman; Workman, Aron; Prudencio, Mercedes; Brown, Hilda; Fromholt, Susan; Valentine, Joan; Whitelegge, Julian; Borchelt, David
Abstract Mutations in superoxide dismutase 1 (SOD1) associated with familial amyotrophic lateral sclerosis induce misfolding and aggregation of the protein with the inherent propensity of mutant SOD1 to aggregate generally correlating, with a few exceptions, to the duration of illness in patients with the same mutation. One notable exception was the D101N variant, which has been described as wild‐type‐like. The D101N mutation is associated with rapidly progressing motor neuron degeneration but shows a low propensity to aggregate. By assaying the kinetics of aggregation in a well‐characterized cultured cell model, we show that the D101N mutant is slower to initiate aggregation than the D101G mutant. In this cell system of protein over‐expression, both mutants were equally less able to acquire Zn than WT SOD1. In addition, both of these mutants were equivalently less able to fold into the trypsin‐resistant conformation that characterizes WT SOD1. A second major difference between the two mutants was that the D101N variant more efficiently formed a normal intramolecular disulfide bond. Overall, our findings demonstrate that the D101N and D101G variants exhibit clearly distinctive features, including a different rate of aggregation, and yet both are associated with rapidly progressing disease. <boxed-text content-type="graphic" id="jnc12451-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text> We sought to better characterize the biochemical features of two SOD1 mutants associated with rapidly progressing disease, the D101G and wild‐type like D101N mutants. We observed using our cell model that that although similarities were observed when comparing the ability to bind metals and resist trypsin digestion, these mutants differed in their ability to initiate aggregation and to form the normal intramolecular disulfide bond. We conclude that these mutants exhibit distinct properties despite producing similar disease phenotypes in patients.